Hope and anxiety: The study of female embodied experience with assisted reproductive technology. (April 2021) - Yu, Chengpu; Li, Wanlin; Deng, Mingfen
Assisted reproductive technology (ART) is hailed as "the holy grail" for infertile patients in the mainstream narrative. The existing studies have clearly demonstrated how external social factors shape how ART is to be used, but they ignore the recipients of the technologies, and especially the experiences of women. Based on an investigation conducted in Z hospital's reproductive center, this article regards embodiment as the methodological orientation for integrating socio-cultural context with female embodied experience in order to show their bio-social entanglement. As fieldwork evidence indicates, ART in practice is far from simple "hope technology"; instead, it throws women into a paradoxical world in which hope and anxiety coexist. Embodied experience, hope, and anxiety are transmitted through the bodies of women, which reveals the inscription of social-cultural context and technical uncertainty on the female body and, meanwhile, women actively learn strategies by which to cope with the technical uncertainty and moral pressures from local culture (including healing the body, folk religion, etc.), so as to hold onto infertility treatment with hope.